Effects of FLIRT on Bubble Growth in Man - Winkler, B. E.; Koch, A.; Schoeppenthau, H.; Ludwig, T.; Tetzlaff, K.; Hartig, F.; Kaehler, W.; Koehler, A.; Kanstinger, A.; Ciscato, W.; Muth, C.-M. (International Journal of Sports Medicine, 2012)
Recompression during decompression has been suggested to possibly reduce the risk of decompression sickness (DCS). The main objective of the current study was to investigate the effects of FLIRT (First Line Intermittent Recompression Technique) on bubble detection in man. 29 divers underwent 2 simulated dives in a dry recompression chamber to a depth of 40 msw (500 kPa ambient pressure) in random order. A Buehlmann-based decompression profile served as control and was compared to an experimental profile with intermittent recompression during decompression (FLIRT). Circulating bubbles in the right ventricular outflow tract (RVOT) were monitored by Doppler ultrasound and quantified using the Spencer scoring algorithm. Heat shock protein 70 (HSP70), thrombocytes, D-Dimers and serum osmolarity were analyzed before and 120 min after the dive. Both dive profiles elicited bubbles in most subjects (range Spencer 0–4). However, no statistically significant difference was found in bubble scores between the control and the experimental dive procedure. There was no significant change in either HSP70, thrombocytes, and D-Dimers. None of the divers had clinical signs or symptoms suggestive of DCS. We conclude that FLIRT did not significantly alter the number of microbubbles and thus may not be considered superior to classical decompression in regards of preventing DCS.
Keywords: decompression sickness DCS; decompression illness DCI; bubble count; SCUBA diving; recreational diving; FLIRT First Line Intermittent Recompression Technique